The Best plays of 1973-1974 - Mantle, Burns, 1873-1948.; Guernsey, Otis L., 1918-; Storey, David, 1933-; McNally, Terrence; Hopkins, John, 1931-1998.; t; Freeman, David, 1945-; Coward, Noel, 1899-1973.; Stoppard, Tom.; Simon, Neil.; Medoff, Mark Howard; Moore, Edward J. (New York : Dodd, Mead, 1974)
Complete broadway and off-Broadway programs, directories of London, Paris, cross-country, off-off-Broadway theater, 19734-74 statistics, articles, photos.
The contractor / David Storey -- Bad habits / Terrence McNally -- Find your way home / John Hopkins -- Short eyes / t
Includes an index.
Contains ABRIDGED EDITIONS of the ten best plays for 1973-74.
"The best plays, 1894-1973" : p. 434-447.
Keywords: Theater -- United States -- Periodicals; Drama -- 20th century